2012
DOI: 10.1063/1.3679168
|View full text |Cite
|
Sign up to set email alerts
|

Note: Percolation in two-dimensional flexible chains systems

Abstract: A simple model of stiff and flexible polymer chain adsorption: The influence of the internal chain architecture

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 22 publications
(17 reference statements)
0
20
0
Order By: Relevance
“…being A 1 = θ j (∞) = 0.4045 (19) the result for the limit coverage of a simple cubic lattice by infinitely long k-mers. In addition, A 2 = 2.63(5) and A 3 = −5.2 (2).…”
Section: Simulation Results: Random Sequential Adsorption Of Straightmentioning
confidence: 99%
See 1 more Smart Citation
“…being A 1 = θ j (∞) = 0.4045 (19) the result for the limit coverage of a simple cubic lattice by infinitely long k-mers. In addition, A 2 = 2.63(5) and A 3 = −5.2 (2).…”
Section: Simulation Results: Random Sequential Adsorption Of Straightmentioning
confidence: 99%
“…On the basis of the behavior of θ j vs. k in the range 2 ≤ k ≤ 64, and the best fit to this curve, the expression θ j (k) = A 1 + A 2 /k + A 3 /k 2 was found, being A 1 = θ j (∞) = 0.4045 (19) the result for the limit coverage of a simple cubic lattice by infinitely long k-mers. In addition, A 2 = 2.63(5) and A 3 = −5.2(2).…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that the percolation threshold depends on the local chain density N /〈 S 2 〉 ( N is the chain length and S the radius of gyration) and therefore, the percolation threshold depends on the chains' fractal dimension. It was also shown that the RSA method gives quite different results for longer chains and that it was rather ineffective for studies of larger and irregular objects 16, 31…”
Section: Introductionmentioning
confidence: 99%
“…[50][51][52][53] It has recently been shown that the RSA is not a suitable method for studies of the percolation process in systems containing long fl exible chains (and other large and irregular objects) because it becomes ineffi cient for longer macromolecules and percolation thresholds obtained via this method are rather underestimated. [ 28,54 ] Therefore, we have developed and employed the cooperative motion algorithm (CMA) for studies of 2D lattice models containing macromolecules and explicit solvent molecules. [ 47,48 ] Contrary to above-mentioned works, we focus on coarse-grained models of heterpolymer chains consisting of two types of beads.…”
Section: Macromolecular Theory and Simulationsmentioning
confidence: 99%